Axonal signals regulate the differentiation of non-myelin-forming Schwann cells: an immunohistochemical study of galactocerebroside in transected and regenerating nerves - Jessen, KR (J Neurosci, 1987)
Little is known about the factors involved in directing and maintaining the divergent differentiation of the 2 major Schwann cell variants, myelin and non-myelin-forming cells, in peripheral nerves. There is strong evidence that the differentiation of myelin-forming cells depends critically on cell-cell signaling through contact with appropriate axons. In this paper we ask whether this remarkable dependence of the Schwann cell on axonal contact for full differentiation is unique to those cells that form myelin or whether axonal signaling is also an important factor in the differentiation of non-myelin-forming Schwann cells. Sciatic nerves or cervical sympathetic trunks of adult rats were either transected or crushed and the axons allowed to degenerate and, in the case of crushed nerves, to regenerate into the distal stump for periods of time varying from 2 d to 9 weeks. The distal stump of the nerve was excised at specific times, the Schwann cells dissociated and immunolabeled with antibodies to galactocerebroside. In the sciatic nerve, which contains a mixture of non-myelin-forming and myelin-forming Schwann cells, transection resulted in a loss of galactocerebroside expression from the surface of all the Schwann cells in the distal stump over a 9 week period, irrespective of their original phenotype. In crushed sciatic nerves, where axons were allowed to regrow into the distal stumps, the number of Schwann cells expressing immunohistochemically detectable quantities of galactocerebroside in the stump declined over the first 3 weeks, but by 9 weeks after crush the total percentage of galactocerebroside- positive cells in the nerve had risen to control levels.(ABSTRACT TRUNCATED AT 250 WORDS)